Mastery of Information Technology and Organizational Learning Culture Impact on Job Performance in Education Institute Sabilillah East Java (Economic and Bussiness Faculty, Dr Soetomo University, 2020)
The purpose of this study was to examine and analyze the impact mastery of information technology, organizational learning culture, job satisfaction and organizational commitment impact on job performance. The method to analyze data is structural equation modeling. Based on the analysis found that: First, information technology positive effect on job satisfaction. Second, organizational learning negative effect on job satisfaction. Third, job satisfaction is not significant positive effect on organizational commitment. Fourth, organizational learning positive effect on organizational commitment. Fifth, information technology positive effect on organizational commitment. Sixth, information technology negative effect on job performance. Seventh, organizational learning positive effect on job performance. Eighth, organizational commitment positive effect on job performance. Ninth, job satisfaction positive effect on job performance. The results of this study are expected to provide new findings which will enrich the theory of human resource management and behavioral theory of educational institutions, especially with regard to job performance